The Synthesis and Biological Evaluation of Indolactam Alkaloids - Mendoza, Manuel; Eom, Ryan; Salas, Celeste; Haynes-Smith, Jeremy; Billingsley, Kelvin L. (Synthesis, 2019)
In this work, we execute a general synthetic strategy to access novel indolactam alkaloids, which are agonists of protein kinase C. This protocol allowed for the most efficient reported syntheses of indolactam V (ILV) stereoisomers, while also affording the large-scale production of natural product (–)-ILV. Structure–activity studies were conducted with these compounds to elucidate the elements necessary to promote PKC-mediated cellular response. EC50 measurements in leukemia and lymphoma cell lines, as well as molecular docking analyses with the PKCδ C1B domain, provided the foundation for these studies. A distinct correlation between in vitro activity and the conformation of the macrocyclic lactam ring was discovered, which can guide design efforts for therapeutics that target the PKC regulatory domain.
Keywords: natural products; synthesis; indolactams; amino acids; protein kinase C